Resíduo da mineração de calcário laminado na melhoria da fertilidade do solo, no desenvolvimento e na nutrição de plantas - Vasques, Victor Viana (2018)
The laminated limestone that composes the stratigraphy of the Araripe Basin, belonging to the Crato Member of the Santana Formation, is commercially known as Pedra Cariri and has been explored for more than 70 years as ornamental rock. In the municipality of Nova Olinda - CE, one of the state's largest producers, this exploration has caused a series of environmental impacts due to the high generation and stock of high amounts of residues in the locality. The objective of this research was to evaluate the possibility of using Pedra Cariri residues powder in the liming process, where it was evaluated the effects of the incorporation of this limestone on soil fertility and the development, nutrition and productivity of cultivated plants on this ground. The experiment took place in two phases: in the first one there was liming in pots and cultivation of lettuce seedlings; in the second stage there was liming in open area and bean cultivation. The treatments (T) consisted of: control, or without application of limestone (T1); 50% (T2), 100% (T3) and 200% (T4) of the recommended dose, and in the first phase of the experiment there was still a treatment (T5) with application of commercial limestone for comparative purposes. Were cultivated lettuce cv Lucy Brown and cowpea (Vigna unguiculata (L.) Walp) crioula range. The Pedra Cariri residue presented potential for use because, in both experiments, it was efficient in the correction of soil acidity, raising the pH and reducing the exchangeable acidity, potential acidity and percentage of saturation by aluminum. In the first experiment, liming still caused an increase in Ca contents and soil saturation. In the second experiment, liming caused changes in the potassium, magnesium, sulfur, iron and manganese contents in the plant tissue of the beans. There was no effect of liming on lettuce development or on bean productivity. No toxicity or nutrient deficiency symptoms were detected in plants.